Evidence of Enhanced Ion Transport in Li‐Rich Silicate Intercalation Materials. Issue 11 (17th January 2017) - Billaud, Juliette; Eames, Christopher; Tapia‐Ruiz, Nuria; Roberts, Matthew R.; Naylor, Andrew J.; Armstrong, A. Robert; Islam, M. Saiful; Bruce, Peter G.
Abstract : The silicate compounds Li2 MSiO4 (where M = Mn, Fe, Co) have received significant attention recently as Li intercalation electrodes. Overwhelmingly they exhibit relatively poor kinetics of ion intercalation. By synthesizing Li‐rich solid solutions of the form Li2+2 x Fe1− x SiO4 (with 0 ≤ x ≤ 0.3), the structural requirements for fast ion transport and hence relatively fast intercalation have been identified. Specifically the presence of additional Li + in interstitial sites, not normally occupied in the stoichiometric Li2 FeSiO4 compound, enhances ion transport by more than two orders of magnitude. The results, obtained by combining electrochemical measurements, with powder X‐ray and neutron diffraction and atomistic modeling of the ion dynamics, provide valuable guidance in designing future intercalation electrodes with high Li‐ion transport and, hence, fast electrode kinetics. Abstract : Li2+2 x Fe1− x SiO4 compounds ( x = 0 – 0.3) exhibiting a strong polymorphism depending on their composition are reported. Li2.6 Fe0.7 SiO4 compound exhibits enhanced lithium electrode kinetics, allowing for high rates of charging and discharging to be achieved. In this work, computational methods are combined with electrochemistry and neutron diffraction to characterize lithium‐rich iron silicate compounds, used as cathodes for lithium‐ion batteries.